Materials structure & micromechanics of fracture IV MSMF-4 : proceedings of the fourth International Conference on Materials Structure & Micromechanics of Fracture, Brno, Czech Republic, June 23-25, 2004 - Pokluda, Jaroslav (Materials science forum, 2005)
This volume contains papers selected from the more than 120 contributions presented during the 4th international conference on "Materials Structure & Micromechanics of Fracture (MSMF-4)", in Brno, Czech Republic, June 23-25, 2004. The MSMF-4 conference successfully carried on the tradition of previous conferences. Nearly 150 scientists from 21 countries presented a variety of multiscale approaches to the modeling and testing of deformation and fracture processes in engineering materials. In collaboration with the International Advisory Board, the organizers also asked Prof. A. J. McEvily (University of Connecticut, USA), Prof. W. Dietzel (GKSS-Forschungszentrum Geesthacht GmbH, Germany), Prof. G. E. Beltz (University of Santa Barbara, California, USA) and Prof. T. Kitamura (Kyoto University, Japan) to prepare plenary key-note lectures. In addition, other leading scientists were asked to provide key-note lectures for each section. The resultant papers, ordered approximately in a sequence going from atomistic to mezoscopic to macroscopic, are presented in the first section of these proceedings. The contributed papers are similarly ordered in the second section. The main goal of the book was to demonstrate a variety of multiscale approaches, ranging from atomistic to macroscopic levels, and in this it succeeds admirably.